(3GdehTM (B((3aj eBNP GdYdeGA Ydi GdTYQGA(B)s - (3eMeO Hf YeQGf Hf ehSi, CHh YHjO Gddg GdnerQoRHGfj,J (B384 (3g` s ((3eMeO eMehO Hf GdJdGejO GdJQcRi GdJTfbjWi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG Chdi ef LRjd YWGFg SCdJ MQS Gddg GdfYeg Ydjc s
(3BNQgG (B:s
(3jehJ QOF GdTYQ ef bHd Cgdg hLjOg jHbi hEf eGJ bGFdg s
(3GdfSNI efbhdI ef fSNI GdhRjQ eMeO GdYdbei ef fSNI YHOGdSdGe Hf GdMSjf GdHUQi GdefbhdI ef fSNI GdeDdas
(3HChdgG JQLeg ddeDda fbdgG HNWg GdfGSN GdTfbjWi ef cJGH EfHGg GdQhGI Ydi CfHGI GdfLGI hHChdgG HNW eNGda agQSGJ ddTYQGA hafhf GdTYQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs